Análise genômica durante a epitelização após neovaginoplastia na síndrome Mayer-Rokitansky-Kuster-Hauser - Lucio, Juliane Dornelas [UNIFESP] (2019)
Objectives: To evaluate the genes markers of activity of stem cells differentially expressed during the process of vaginal epithelialization in Mayer-Rokitansky-Küster- Hauser syndrome. Methods: Serial vaginal biopsies were performed in 5 patients who underwent neovaginoplasty using the McIndoe technique with oxidized cellulose. Transcriptomic analysis of 84 specific marker genes from the process of differentiation and stem cell signaling was performed using the real-time Polymerase Chain Reaction technique. Statistical analysis and graphs were performed MetaboAnalyst R version 3.4.3. Results: Using the Pearson correlation analysis and FDR, differentially expressed genes were identified between samples at surgery and 6 months after surgery. The expression of the FGF3 / PDX1, CD8A / PDX1, DHH / PDX1, PDX1 / CD8A, ALPI / DHH, PDX1, CD8A and PDX1 / COL2A1 genes presented statistical significance (p ≤ 0.05). Conclusion: The present study identified certain genes and biological pathways, which may be associated with neovagine healing and may assist in fundamental research and treatment in the future.